2022
DOI: 10.1186/s40168-022-01364-2
|View full text |Cite
|
Sign up to set email alerts
|

Mining the microbiota to identify gut commensals modulating neuroinflammation in a mouse model of multiple sclerosis

Abstract: Background The gut microbiome plays an important role in autoimmunity including multiple sclerosis and its mouse model called experimental autoimmune encephalomyelitis (EAE). Prior studies have demonstrated that the multiple sclerosis gut microbiota can contribute to disease, hence making it a potential therapeutic target. In addition, antibiotic treatment has been shown to ameliorate disease in the EAE mouse model of multiple sclerosis. Yet, to this date, the mechanisms mediating these antibio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 122 publications
0
15
0
Order By: Relevance
“…The abundance of this genus relative to the geometric mean of each sample suggests that high abundance will push samples to be less lesion-like. This is an encouraging result since work has shown that an elevated abundance of Anaerotruncus , a butyrate producer, may exert a protective effect by inhibiting glucose transport and glycolysis (65,66). Additional support for our method comes from the results of the Crohn’s disease dataset.…”
Section: Discussionmentioning
confidence: 73%
“…The abundance of this genus relative to the geometric mean of each sample suggests that high abundance will push samples to be less lesion-like. This is an encouraging result since work has shown that an elevated abundance of Anaerotruncus , a butyrate producer, may exert a protective effect by inhibiting glucose transport and glycolysis (65,66). Additional support for our method comes from the results of the Crohn’s disease dataset.…”
Section: Discussionmentioning
confidence: 73%
“…The abundance of this genus relative to the geometric mean of each sample suggests that high abundance will push samples to be less lesion-like. This is an encouraging result, since work has shown that an elevated abundance of Anaerotruncus , a butyrate producer, may exert a protective effect by inhibiting glucose transport and glycolysis ( 50 , 51 ). Additional support for our method comes from the results of the Crohn’s disease data set.…”
Section: Discussionmentioning
confidence: 76%
“…Although no research has been conducted on the effects of Anaerotruncus on inflammation in osteoarticular disease, Paola Bianchimano et al. discovered that increasing Anaerotruncus in patients with multiple sclerosis (MS) improved the disease, which may be related to the inflammatory suppressive effect of RORγt+ regulatory T cells in mesenteric lymph nodes 34 . The above two intestinal microorganisms' protective effect may be related to their production of short‐chain fatty acids (SCFA) 33,35 …”
Section: Discussionmentioning
confidence: 99%
“…discovered that increasing Anaerotruncus in patients with multiple sclerosis (MS) improved the disease, which may be related to the inflammatory suppressive effect of RORγt+ regulatory T cells in mesenteric lymph nodes. 34 The above two intestinal microorganisms' protective effect may be related to their production of short-chain fatty acids (SCFA). 33,35 SCFA has an important regulatory effect on the human body's energy homeostasis and immune cells' function.…”
Section: Discussionmentioning
confidence: 99%